The effect of intravenous adrenaline on electrocardiographic changes during resuscitation in patients with initial pulseless electrical activity in out of hospital cardiac arrest. (March 2019) - Skjeflo, Gunnar Waage; Skogvoll, Eirik; Loennechen, Jan Pål; Olasveengen, Theresa Mariero; Wik, Lars; Nordseth, Trond
Abstract: Introduction: Presence of electrocardiographic rhythm in the absence of palpable pulses defines pulseless electrical activity (PEA) and the electrocardiogram (ECG) may provide a source of information during resuscitation. The aim of this study was to examine the development of ECG characteristics during advanced life support (ALS) from Out-of-hospital cardiac arrest (OHCA) with initial PEA, and to explore the potential effects of adrenaline on these characteristics. Methods: Patients with OHCA and initial PEA, part of randomized controlled trial of ALS with or without intravenous access and medications, were included. A total of 4840 combined observations of QRS complex rate (heart rate) and width were made by examining defibrillator recordings from 170 episodes of cardiac arrest. Results: We found Increased heart rate (47 beats per minute) and reduced QRS complex width (62 ms) during ALS in patients who obtained return of spontaneous circulation (ROSC); while patients who received adrenaline but died increased their heart rate (22 beats per minute) without any concomitant decrease in QRS complex width. Conclusion: ECG changes during ALS in cardiac arrest were associated with prognosis, and the administration of adrenaline impacted on these changes.